2020
DOI: 10.1016/j.scog.2019.100142
|View full text |Cite
|
Sign up to set email alerts
|

Metacognitive function and fragmentation in schizophrenia: Relationship to cognition, self-experience and developing treatments

Abstract: Bleuler suggested that fragmentation of thought, emotion and volition were the unifying feature of the disorders he termed schizophrenia. In this paper we review research seeking to measure some of the aspects of fragmentation related to the experience of the self and others described by Bleuler. We focus on work which uses the concept of metacognition to characterize and quantify alterations or decrements in the processes by which fragments or pieces of information are integrated into a coherent sense of self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
137
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 103 publications
(153 citation statements)
references
References 108 publications
(122 reference statements)
4
137
0
1
Order By: Relevance
“…The potential importance of metacognitive deficits as a treatment target in psychosis comes from multiple sources. As summarized in recent reviews, 19,20 cross cultural studies using the MAS-A have found that persons with psychosis experience deficits in metacognition relative to healthy controls 32 and individuals who experience significant medical but not psychiatric adversity. Differing profiles of metacognitive function have also been observed in persons diagnosed with various conditions including schizophrenia, 32,33 borderline personality disorder, 34 bipolar disorder, 35 depression, 36 PTSD, 37 and substance use disorders.…”
Section: Metacognitive Impairment and Psychopathologymentioning
confidence: 99%
See 2 more Smart Citations
“…The potential importance of metacognitive deficits as a treatment target in psychosis comes from multiple sources. As summarized in recent reviews, 19,20 cross cultural studies using the MAS-A have found that persons with psychosis experience deficits in metacognition relative to healthy controls 32 and individuals who experience significant medical but not psychiatric adversity. Differing profiles of metacognitive function have also been observed in persons diagnosed with various conditions including schizophrenia, 32,33 borderline personality disorder, 34 bipolar disorder, 35 depression, 36 PTSD, 37 and substance use disorders.…”
Section: Metacognitive Impairment and Psychopathologymentioning
confidence: 99%
“…In this vein, MERIT explicitly proposes that metacognitive processes may represent just such a set of quantifiable phenomena which underlie self-experience. 19,20 Since its introduction as a psychological construct over 40 years ago, metacognition has been described as a set of multilevel processes involved in thinking about one's own mental or internal experiences. 21,22 MERIT relies on the integrative model of metacognition, which proposes that metacognition can be characterized as a spectrum of mental activities.…”
Section: Metacognition Self-experience In Psychosis and Meritmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based on the Metacognition Assessment Scale (MAS; Semerari et al, 2003Semerari et al, , 2007, a tool to assess frequency of metacognitive acts within psychotherapy transcripts. MAS-A follows its main construction of sub-dimensions, but was adapted to interview situations and particularly emphasizes increasing complexity of single metacognitive acts (Lysaker et al, 2020). Four implied sub-dimensions represent semi-independent metacognitive capacities, namely self-and other reflection (S-Scale: "Understanding of One's Mind, " O-Scale: "Understanding of Other's Mind), perspective-taking (D-Scale: "Decentration") and the overall capacity to integrate and use metacognitive knowledge to master intrapsychic and interpersonal challenges adopting a psychologically minded stance (M-Scale: "Mastery").…”
Section: Instruments Clinical Interviewmentioning
confidence: 99%
“…This later component has been named meta-awareness, and research has demonstrated that individuals are only intermittently aware of the fact that their minds have disengaged from the external world. Research exploring the meta-awareness of MW in schizophrenia should have in mind that deficits in metacognition are common in schizophrenia 30 . Metacognition implies self-conscious awareness and reflection about one's own cognitive events.…”
mentioning
confidence: 99%